Spatial Cognition through a Nonvisual Experience - Tunçok Sarıberberoğlu, Mine; Tarçın Turgay, Zeynep; Çanakçıoğlu, Nevşet Gül (ICONARCH International Congress of Architecture and Planning, 2017)
The notion examining the interaction between the individual and the physical setting is the concept of perception, which is evaluated by Hall (1966) as the main competence that living organisms possess for survival. In this manner, perceptual product can be defined as the result of perceptual processes through which the stimuli from the environment are converted into cognitive data by the receptor cells of sense organs - mainly the eye. According to Pallasmaa (2005), the eye became the centre of the perceptual world through the invention of perspectival representation, which turned into a symbolic form both describing and conditioning perception. Also, such concepts as Merleau-Ponty’s (2005) bodily experience, a classification of perceptual modalities, have been partly replaced by more holistic approaches, considering the experience as the most essential factor of the physical setting which is defined as the collection of cognitive data of individuals formed by various information processing circumstances (Downs and Stea, 2011). Cognitive mapping is the process of a mental representation which people acquire, code, store, recall and decode information about the relative location and attributes of the physical setting (Downs and Stea 2011). This imaged information includes impressions about structure or appearance of a place, its relative location, its use and its values. On the other hand, a specific place’s structure, value and relative relations can be analysed in a more analytical way. Space syntax is a method for describing and analysing the relationships between spaces and a set of techniques for the representation, quantification, and interpretation of spatial relations in buildings and settlements. Contributing to this debate, this paper explores the cognitive data generated by sighted people in a non-visual bodily experience, as they are guided through “Dialogue in the Dark”, a thematic environment consisting of completely dark rooms equipped with scent, sound, wind and tactile simulations of a specific urban setting and syntactic relations of that space. In this regard, a two-step methodology is applied: the first step comprises cognitive data from the cognitive maps drawn by participants just after their experience, while the second one comprises existing spatial data revealed by syntactic analyses. Finally, the correlation between the cognitive frequencies of the experienced nodes in each cognitive map and the syntactic values of the setting are statistically analysed. Statistical outcomes show that without vision, no correlation is found between the syntactic values and the frequency of spaces but, auditive and tactile characteristics of the spaces are significantly correlated with the frequencies of the spaces. In conclusion, the results show that spatial cognition without vision is mainly dependent on bodily experience of the self which is stimulated mostly by auditive and tactile senses, and also that the effect of the syntactic characteristics of the space derived from visual parameters loosens the ties with the notion of spatial cognition.